A hit zenei szimbólumai - Liszt Christus és Brahms: Német requiem című művében - Illés Mária (Szegedi vallási néprajzi könyvtár, 2009)
The two 19th century oratorios in question were composed in the same decade - one by a Catholic, the other by a Lutheran composer. In both cases, the text of the oratorio was taken from the Bible by the composer himself. In these compositions which are not representing a liturgical genre, both composers draw on the liturgical tunes of their respective religions, which is the first musical sign of religious orientation. Oratorios comprise, on the one hand, elements pertaining to religious faith, such as musical number symbolism and a fugal structure associated with the genre since the Baroque era; on the other hand, we also find the plain and commonly used musical elements of the 19th century, such as ethereal, pastoral and demonic musical topoi, which now serve religious purposes. By using such forms of express musical symbolism, new intertextual connections are established. This paper attempts to interpret this additional layer of content, and the peculiar meaning enforced by the "emotional determination" of music through the examination of musical devices.